APPLICATION OF VERBAL BEHAVIOR METHOD (ABA-VB) FOR CHILDREN WITH SPEECH DELAY DISORDERS - Hasballah, Maria Ulfa; Barmawi, Barmawi; Hock, Kway Eng (Psikoislamedia: Jurnal Psikologi, 2023)
Speech delay is disorder that attacks the speech organs so that speech delays occur in children who have entered the speaking up. Speech delay disorder is seen as a disorder that most often affects children. The reasons for this disturbance also, starting from internal and external factor. Internal factors are more concerned with the physiological condition of the child. It is likely that the child has a disorder that he carries from birth. The external factors can be obtained environment and play. Verbal Behavior was introduced by Skinner where research on verbal behavior began in 1935, verbal behavior aims to apply language skill that children have, with a richer language vocabulary of communication for children with their environment. The purpose of this study was to see the effectiveness of the verbal behavior method (ABA-VB) which is applied to children with speech delay disorder at Bintang Kecil therapy center. The research location is at Bintang Kecil therapy center, Banda Aceh, Indonesia. This study uses experimental techniques the one group pretest posttest with single research subject (SSR), which is an approach that provides treatment to one research group using only one research subject, then the result will be calculated the difference. The treatment uses is to provide the ABA-VB method treatment. This research analysis uses descriptive statistics by using graphs to see changes in learning outcomes. The result of this study is that there is a significant increase in verbal ability in children with speech delay disorder. This research can be used as a reference for target subjects, and a support for the application of the ABA-VB method to children with speech delay disorder that are balanced with balance disorders in various theraphy center and special schools for children with special needs in Banda Aceh, Indonesia.